Effect of different radiation dose levels on the lipid oxidation, microbiological quality and some physical characteristics of pre-cooked pork loin - Pascual, Catherine R.; Acevedo, Teresita P. (1969.)
Pre-cooked pork loin, 1 cm thick and vacuum packed, were subjected to different gamma radiation dose levels of 0, 2.8, 3.8 and 4.8 Megarads. The control (0 Mrad) was stored at -4 °C while the irradiated samples were stored at 5±2°C. Storage period was 31 days. Objective testsl like measurement of peroxide value, total carbonyl compounds and free fatty acid value were conducted on the 0, 3rd and every seven days during storage. Subjective evaluation was performed by five semi-trained judges. They evaluated the samples according to the intensity of discoloration, off-odor, irradiation flavor, off-flavor, mushiness and friability. The samples were evaluated on the 0, 17th and 31st day of storage. The microbiological quality of the samples were evaluated by total plate count. Total plate count was conducted at the beginning, middle and end of the storage period. Scores for irradiation flavor and odor were subjected to statistical analysis using rank analysis. Correlation between total carbonyl compounds and off-odor and irradiation flavor was made using a rank correlation method.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Meat -- Radiation preservation; Meat -- Preservation